Modelling the Nexus between Financial Development, FDI, and CO2 Emission: Does Institutional Quality Matter? - Festus Fatai Adedoyin; Festus Victor Bekun; Kayode Kolawole Eluwole; Samuel Adams (Energies, 2022)
The present study draws motivation from the United Nations Sustainable Development Goals, with a special focus on SDGs 7 and 13, which highlight the need for access to clean and affordable energy in an environment devoid of emissions; it addresses climate change mitigation in the context of Sub-Saharan Africa. To this end, a carbon-income function setting for Sub-Saharan Africa (SSA) is constructed. The dynamic relationship between financial development and climate change is evaluated using three indicators and foreign direct investment and carbon dioxide emissions (CO2), while accounting for regulatory institutional quality using a “generalized method of a moment” estimation technique that addresses both heterogeneous cross-sectional issues. Empirical results obtained showed a positive statistical relationship between economic growth and CO2 emissions in SSA at the <0.01 significance level. This suggests that, in SSA, the economic growth path is pollutant emissions driven. This indicates that SSA is still at the scale phase of her growth trajectory. However, an important finding from the present study is that regulatory institutional indicators, such as political stability, government effectiveness, control of corruption, and voice and accountability, all exert a negative effect on CO2 emissions. This implies that regulatory measures militate against emissions in SSA. Based on the empirical findings of this study, it can be concluded that clean FDI inflows assist in ameliorating emissions. Thus, the need for a paradigm shift to cleaner technologies, such as renewables, that are more eco-friendly, is encouraged in Sub-Saharan Africa, as the current study demonstrates the mitigating role of renewable energy consumption on CO2 emissions. Further policy prescriptions are presented in the concluding section.